EFL Students’ Achievement in Reading Comprehension through Gamification Kahoot - Putri Lisa Anggraini; Sayit Abdul Karim; R. Yohanes Radjaban (Faculty of Language and Literature, University of Surakarta, 2023)
This study attempts to examine EFL students’ achievement in reading comprehension of recount text through gamification Kahoot, a technological-based learning platform, as well as to explore their perceptions of using gamification Kahoot as an assessment tool in the reading test. The data were obtained from both tests and questionnaires, and the assessment criteria used as proposed by Kartika (2001), and uses descriptive analysis. Meanwhile, the students’ perceptions are based on the indicator theory of perceptions proposed by Hamka (2002). 36 students (21 females, and 15 male students) in the tenth grade of the State Vocational High School 1 Godean in the academic year 2022/2023 participated as the respondents. The findings revealed that the highest score on the test was 100 and the lowest score was 53. Meanwhile, the average or mean of the student's score is 74 with a total score of 2664. Furthermore, the achievement of students in reading comprehension of recount text using gamification Kahoot is in the